Countercyclical Fiscal Policy and Gender Employment : Evidence from the G-7 Countries - Akitoby, Bernardin; Honda, Jiro.; Miyamoto, Hiroaki (Washington, D.C. : International Monetary Fund, 2019)
Would countercyclical fiscal policy during recessions improve or worsen the gender employment gap? We give an answer to this question by exploring the state-dependent impact of fiscal spending shocks on employment by gender in the G-7 countries. Using the local projection method, we find that, during recessions, a positive spending shock of 1 percent of GDP would, on average, lift female employment by 1 percent, while increasing male employment by 0.6 percent. Consequently such a shock would improve the female share of employment by 0.28 percentage point during recessions. Our findings are driven by disproportionate employment changes in female-friendly industries, occupations, and part-time jobs in response to fiscal spending shocks. The analysis suggests that fiscal stimulus, particularly during recessions, could achieve the twin objectives of supporting aggregate demand and improving gender gaps.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet